PEMIKIRAN PENDIDIKAN ISLAM AHMAD SYAFII MAARIF - Ali, Mohamad (Universitas Muhammadiyah Surakarta, 2016)
The Indonesian Islamic intellectualism is increasingly dynamic and accounted in the global arena. This perception occurs because on the one hand, Indonesia is the largest concentration of Muslim population in the world, and on the other side there is an ontentic, dynamic and inclusive process of Islamic intellectualism. The 1980s Indonesian Islam gave birth to a series of